2022
DOI: 10.3390/dermato2020003
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Performance of the Derived Neutrophil-to-Lymphocyte Ratio in Stage IV Melanoma Patients Treated with Immune Checkpoint Inhibitors

Abstract: The purpose was to evaluate the prognostic performance of the derived neutrophil–to-lymphocyte ratio (dNLR) in patients with metastatic cutaneous melanoma (CM) treated with immune checkpoint inhibitors (ICI). We retrospectively investigated 41 CM patients with stage IV disease who had the indication for treatment with ICI. dNLR as well as NLR were routinely determined prior to the start of ICI treatment. The dNLR and NLR were calculated as follows: dNLR = absolute neutrophil counts (ANC)/white blood cell count… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 32 publications
1
2
0
Order By: Relevance
“…Unlike NLR, multivariate analysis in this study did not reveal any proof of a connection between dNLR and staging, LNM, or DM. NLR and dNLR look identical and have similar effects on cancer-specific mortality [91,92]. Our investigation supported this hypothesis, which found a robust positive correlation between dNLR and NLR (ρ = 0.950, p < 0.001).…”
Section: Discussionsupporting
confidence: 83%
“…Unlike NLR, multivariate analysis in this study did not reveal any proof of a connection between dNLR and staging, LNM, or DM. NLR and dNLR look identical and have similar effects on cancer-specific mortality [91,92]. Our investigation supported this hypothesis, which found a robust positive correlation between dNLR and NLR (ρ = 0.950, p < 0.001).…”
Section: Discussionsupporting
confidence: 83%
“…A survival receiver operating characteristic (ROC) analysis was adopted to identify potential cut-offs that optimally stratify patients into risk groups. Optimal thresholds for blood cell count-derived ratios were determined based on literature reviews [7][8][9][10][11][12][13] and our previous work, where we used those cut-offs and verified their applicability. 14 The cut-off values were set as follows: NLR 3, PLR 160, LMR 2, SII 800 and dNLR 1,9, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple investigations have shown that an increased NLR is associated with poor clinical outcomes in many malignancies, but this parameter has not been thoroughly investigated in CM, except for stage IV, particularly in the context of the use of ICI [ 31 , 33 , 34 ]. Lino-Silva et al [ 35 ] was the first study group investigating NLR in CM stages I–III.…”
Section: Discussionmentioning
confidence: 99%